IDDF2022-ABS-0120 Hepatocyte apoptosis fragment product cytokeratin-18 M30 and non-alcoholic steatohepatitis risk prediction: an international registry study. (2nd September 2022) - Zhang, Huai; Rios, Rafael S; Boursier, Jerome; Anty, Rodolphe; Chan, Wah-Kheong; George, Jacob; Yilmaz, Yusuf; Wong, Vincent Wai-Sun; Sookoian, Silvia; Fan, Jian-Gao; Dufour, Jean-François; Papatheodoridis, George; et al.
Abstract : Background: Liver biopsy for the diagnosis of non-alcoholic steatohepatitis (NASH) is limited by its inherent invasiveness and sampling errors. Some studies have shown that cytokeratin-18 (CK-18) concentrations may be useful in predicting NASH, but results across studies have been inconsistent. The aim of this study was to identify the feasibility of CK-18 M30 concentrations as a non-invasive alternative to liver biopsy for diagnosing NASH. Methods: Using an open online reporting form, individual data were collected from 15 registry centers on patients with biopsy-proven non-alcoholic fatty liver disease (NAFLD), and in all patients circulating CK-18 M30 levels were measured. These data included sex, age, ethnic, hypertension, diabetes, and serum alanine aminotransferase, but not personal health identifier. Individuals with NAFLD activity score (NAS) ≥ 5 including a score of ≥ 1 for each of steatosis, ballooning and lobular inflammation were diagnosed as having definite NASH; individuals with NAS ≤ 2 and no fibrosis were diagnosed as having non-alcoholic fatty liver (NAFL) (simple steatosis). (IDDF2022-ABS-0120 Table 1, IDDF2022-ABS-0120 Table 2). Results: 2716 participants were screened and 1083 participants (172 with NAFL and 911 with NASH) were finally enrolled. Median CK-18 M30 levels were higher in patients with NASH than in those with NAFL (mean difference 150 U/L; standardized mean difference: 0.78 [0.62–0.95]), and there was interaction between CK-18 levels and serum alanine aminotransferase ( P <0.001). CK-18 M30 levels were positively associated with histological NAS in most centers. The AUROC for NASH was 0.728 (95% CI: 0.691–0.764) and the Youden index was 275.7 U/L for CK-18 M30 (IDDF2022-ABS-0120 Figure 1. Diagnostic performances of CK-18 M30 level at the optimal cut-off value of 275.7 U/L. (A) Sensitivity in registry center. (B) Specificity in registry center. (C) Sensitivity in main characteristics subgroup. (D) Specificity in main characteristics subgroup). Sensitivity (54% [51–58%]) and positive predictive value (52%) were both not ideal. Conclusions: This large multicenter registry study shows that CK-18 M30 measurement in isolation is of limited value for predicting NASH.